The meaning of public space of Kupang City Nostalgia Park - Yoseph Liem; Reginaldo Chistophori Lake (ARTEKS : Jurnal Teknik Arsitektur, 2018)
Kupang City Nostalgia Park became one of the characteristics of the city where the park is located in the city center and became the only representative representative park in the city of Kupang. But the soul is unreliable. Is Nostalgic Park able to give meaning to the initial concept of planning and development in order to provide broad benefits for the city of Kupang and its citizens. Therefore, the purpose of the study is to know the extent to which Nostalgia parks as a public space and how its meaning for the citizens of the city. This research was conducted by qualitative descriptive method. Observations were made in the park room at predetermined times to get an overview of the utilization pattern. The results show that the utilization of open space Nostalgia public park is still not maximized according to the initial concept, where the purpose of utilization of the park on a larger scale has not been integrated with the unsuccessful efforts to make the park as the lung of the city / forest city and has not given a democratic meaning to visitors park as a public open space that can be accessed by the visitors.